2022
DOI: 10.3390/math10132230
|View full text |Cite
|
Sign up to set email alerts
|

Learning Analytics and Computerized Formative Assessments: An Application of Dijkstra’s Shortest Path Algorithm for Personalized Test Scheduling

Abstract: The use of computerized formative assessments in K–12 classrooms has yielded valuable data that can be utilized by learning analytics (LA) systems to produce actionable insights for teachers and other school-based professionals. For example, LA systems utilizing computerized formative assessments can be used for monitoring students’ progress in reading and identifying struggling readers. Using such LA systems, teachers can also determine whether progress is adequate as the student works towards their instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Given this situation, the Chinese Ministry of Education recently initiated a series of educational reforms to facilitate learning, and quality assessment is one of these reforming targets (Chinese Ministry of Education, 2004Education, , 2007. Formative assessment is advocated in higher education in China, for it measures students' progress as a process instead of an outcome (Bulut et al, 2022). Feedback, as an integrated part of formative assessment, takes up the largest proportion of the College English classroom assessment in China (Jin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Given this situation, the Chinese Ministry of Education recently initiated a series of educational reforms to facilitate learning, and quality assessment is one of these reforming targets (Chinese Ministry of Education, 2004Education, , 2007. Formative assessment is advocated in higher education in China, for it measures students' progress as a process instead of an outcome (Bulut et al, 2022). Feedback, as an integrated part of formative assessment, takes up the largest proportion of the College English classroom assessment in China (Jin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm is used to calculate the shortest distance between two points (shortest path first, SPF) [29,30]. The coordinate path is saved in matrix form.…”
Section: Dijkstra Spf Algorithmmentioning
confidence: 99%
“…Fourth, depending on the outcomes of the screening procedure, students could be more or less frequently tested based on their academic growth in mathematics throughout the academic year. Previous research showed that students' assessment schedules can be personalized in core subject areas based on their learning progress estimated from Star assessment scores [46][47][48]. Future research can investigate the relationship between screening results and students' academic growth throughout the academic year by following a personalized assessment schedule for students.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%